PENGEMBANGAN MODUL ANATOMI REPTIL DI DAERAH ALIRAN SUNGAI MAOSPATI MAGETAN UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATA KULIAH STRUKTUR HEWAN DI IKIP PGRI MADIUN - Daniel Sugiarto (Florea : Jurnal Biologi dan Pembelajarannya, 2016)
During this time the students learning system, especially on the structure of animals in biology education IKIP PGRI MADIUN. information presented in the form of modules still no or less so difficult to accept students in particular about the material or preparations that are less known as well as local reptile anatomy that is found around the neighborhood students. The aim of developing local reptile anatomy modules in subjects animal structure. Research using 4-Dmodel of development (Define, Design, Develop, Disseminate). Results of development in the form of draft module to be tested and improved understanding of the concept of students. The trial results are obtained material content of the course structure validator experts percentage of 86.66% was obtained animals can be categorized valid (good). The trial results stating that: 1) the modules worth diujicabakan field and very helpful in learning the anatomy of reptiles 2) Students are more familiar with preparations anatomy reptiles as obtained from the student environment and the result of understanding the concept of students with test pre test and posh test through the test T is obtained thitung 15.22> ttable 1,717 or able to enhance student understanding of concepts. Limitations modules developed only compiled on the subject of local reptile anatomy